Theorizing women and leadership : new insights and contributions from multiple perspectives - Storberg-Walker, Julia; Haber-Curran, Paige (Emerald Publishing Limited : Information Age Publishing Inc., 2017)
Theorizing Women and Leadership: New Insights and Contributions from Multiple Perspectives is the fifth volume in the Women and Leadership: Research, Theory, and Practice series. This cross-disciplinary series, from the International Leadership Association, enhances leadership knowledge and improves leadership development of women around the world. The purpose of this volume is to provide a forum for women to theorize about women's leadership in multiple ways and in multiple contexts. Theorizing has been a viewed as a gendered activity (Swedberg, 2014), and this series of chapters seeks to upend that imbalance. The chapters are written by women who represent multiple disciplines, cultures, races, and subject positions. The diversity extends into research paradigm and method, and the chapters combine to illuminate the multiple ways of knowing about and being a woman leader.Twenty-first century leadership scholars acknowledge the importance of context, and many are considering post-heroic leadership models based on relationships rather than traits. This volume contributes to this discussion by offering a diverse array of perspectives and ways of knowing about leadership and leading. The purpose of the volume is to provide readers with not only interesting new ideas about women and leadership, but also to highlight the diverse epistemologies that can contribute to theorizing about women leaders. Some chapters represent typical social scientific practices and processes, while others represent newer knowledge forms and ways of knowing. The volume contributors adopt various epistemological positions, ranging from objective researcher to embedded co-participant. The chapters link their new findings to existing empirical or conceptual work and illustrate how the findings extend, amend, contradict, or confirm existing research. The diversity of the chapters is one of the volume's strengths because it illuminates the multiple ways that leadership theory for women can be advanced.Typically, research based on a realist perspective is more valued in the academy. This perspective has indeed generated robust information about leadership in general and women's leadership in particular. However, readers of this volume are offered an opportunity to explore multiple ways of knowing, different ways of researching, and are invited to de-center researcher objectivity. The authors of the chapters offer conceptual and empirical findings, illuminate multiple and alternative research practices, and in the end suggest future directions for quantitative, qualitative, and mixed-methods research.
Keywords: Leadership in women.; Women in the professions.; Women executives.; Social Science -- Women's Studies.; Gender studies: women and girls.; elektronické knihy; electronic books